2008
DOI: 10.1080/10799890802407120
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-activating Plasma Membrane Receptors and Calcium Signaling in Immortalized Human Airway Epithelial Cells

Abstract: Mechanical clearance of inhaled dust particles and microorganisms is an important part of the innate defense mechanisms of mammalian airways. Airway epithelia are composed of various cell types with different degrees of cell polarity. Serous cells regulate composition and volume of luminal periciliary fluid and mucus. Autocrine, paracrine, or neuronal messengers determine the secretory and reabsorptive rates of electrolytes and water via cAMP-or inositol triphosphate/calcium-mediated intracellular signals. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The 16HBE14o − cells are highly polarized and all known characteristics indicate that these cells represent one type of serous cells at the surface of airway epithelia, whereas the less polarized S9 cells may represent an airway cell type that is derived from the lower layer of the bronchial epithelium [20], [23], [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 16HBE14o − cells are highly polarized and all known characteristics indicate that these cells represent one type of serous cells at the surface of airway epithelia, whereas the less polarized S9 cells may represent an airway cell type that is derived from the lower layer of the bronchial epithelium [20], [23], [29].…”
Section: Discussionmentioning
confidence: 99%
“…S9 cells were originally derived from a cystic fibrosis patient, subsequently corrected by introduction of the gene encoding wild-type cystic fibrosis transmembrane conductance regulator (CFTR) through adenoviral transfer. 16HBE14o − cells were derived from the bronchial epithelium of a transplant patient, express wild-type CFTR and are commonly used for analysis of a polarized cell layer [20], [23].…”
Section: Methodsmentioning
confidence: 99%
“…One cancer cell line (A549) of alveolar origin was used for comparison. 16HBE14o-cells were derived from normal bronchial epithelium, form high resistance epithelia-like cell monolayers with tight junctions and apical surface specializations and show responses to a variety of external stimuli that are very similar to those obtained in freshly isolated primary bronchial epithelial cells (Cozens et al, 1994;Gruenert et al, 2004;Eichstaedt et al, 2008). S9 cells were derived from a cystic fibrosis patient and had been corrected by introduction of the gene encoding wild-type cystic fibrosis transmembrane conductance regulator (CFTR) (Zeitlin et al, 1991;Flotte et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…S9 cells were derived from a cystic fibrosis patient and had been corrected by introduction of the gene encoding wild-type cystic fibrosis transmembrane conductance regulator (CFTR) (Zeitlin et al, 1991;Flotte et al, 1993). They show many characteristics of bronchial cells involved in salt and water secretion (Eichstaedt et al, 2008). A549 cells are lung cancer cells derived from surfactant secreting type II pneumocytes (Lieber et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…We used the immortalized human bronchial cell lines S9 and 16HBE14o-as model systems to study signaling effects of bacterial toxins because these cells may represent different types of airway epithelial cells and appear to have maintained many of the structural and functional characteristics of the original airway epithelial cells (10,12,15,22,56). The experiments revealed that some effects of bacterial factors on airway epithelial cell signaling were common to both types of cells while others were different, indicating that interaction of bacterial factors with host cells may be highly cell type specific.…”
mentioning
confidence: 99%